Method for enriching carbon dioxide in cement kiln tail gas and co-producing nano calcium carbonate

The cement kiln exhaust gas enriches carbon dioxide and reacts with calcium oxide or calcium hydroxide to prepare nano-calcium carbonate, which solves the problems of carbon emissions and the lack of profit models in the cement industry, achieves carbon emission reduction and efficient production of by-products, and improves product quality and cost-effective.

CN119263334APending Publication Date: 2025-01-07SHANNENG NEW MATERIALS (ZIBO) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411824449.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The cement industry has a large carbon emissions and is difficult to reduce emissions. The existing technology is difficult to effectively utilize carbon dioxide in exhaust gas, and lacks a profit model.

Method used

Nanocalcium carbonate is prepared by enriching carbon dioxide by cement kiln exhaust gas and reacting with purchased calcium oxide or calcium hydroxide. Pretreatment, adsorption, preparation and carbonization reaction processes are used to produce surface hydrophobic active nanocalcium carbonate.

Benefits of technology

It has achieved carbon emission reduction and the production of by-product calcium carbonate, which has improved production efficiency and product quality, reduced costs, provided a profit model, and is suitable for multiple industrial fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263334A_ABST
    Figure CN119263334A_ABST
Patent Text Reader

Abstract

The invention provides a method for enriching carbon dioxide in cement kiln tail gas and co-producing nano calcium carbonate, and mainly relates to the field of enrichment and reutilization of carbon dioxide in the cement kiln tail gas. After the cement kiln tail gas carbon dioxide is enriched through a physical adsorption method, the volume concentration of the cement kiln tail gas carbon dioxide reaches 35%-45%; and reacting with a 7-20% calcium hydroxide solution at the temperature of 18-35 DEG C to generate nano calcium carbonate. Compared with the traditional method for preparing nano calcium carbonate after producing calcium oxide by using a lime kiln, the method has the advantages of environmental friendliness, lower energy consumption and higher carbon capture and utilization benefits. The method can be used for preparing various crystal forms of nano calcium carbonate; the primary particle size is 40-100 nm, the apparent particle size D97 is smaller than or equal to 9 microns, and the product obtained through the method serves as functional filler and is widely applied to the industrial fields of rubber, plastic, silicon rubber and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention mainly relates to the field of enrichment and reuse of carbon dioxide in cement kiln tail gas, and specifically is a method for enriching carbon dioxide from cement kiln tail gas and co-producing nano calcium carbonate. Background Art

[0002] As one of the industries with the largest carbon emissions in my country (1.23 billion tons of CO2 emissions in 2020, of which about 63% of CO2 emissions came from carbonate decomposition and about 35% from coal burning), the cement industry is difficult to reduce carbon emissions and faces very severe challenges in today's context of energy conservation and emission reduction.

[0003] Carbon capture and purification technology can capture a large amount of CO2 in tail gas emissions, and is a feasible method for reducing greenhouse gas emissions and slowing global warming on a large scale in the future. As a major carbon emitter, the cement industry has the characteristics of large emissions during the process and limited emission reduction at the source, and has a long way to go on the road of carbon emission reduction.

[0004] In addition, how to further utilize the carbon emissions of the cement industry so that it covers the cost of carbon emission reduction or even makes a profit is an important research topic.

[0005] In this context, research on cement kiln exhaust gas capture and enrichment of carbon dioxide technology can provide the "carbon" element for the production of nano-calcium carbonate. By centrally purchasing quicklime or calcium hydroxide from larger steel mills and cement plants to provide the "calcium" element for the production of nano-calcium carbonate, we can achieve the goal of carbon emission reduction and produce by-products for profit, killing two birds with one stone. Summary of the invention

[0006] In order to solve the deficiencies of the prior art, the present invention provides a method for enriching carbon dioxide from cement kiln tail gas and co-producing nano-calcium carbonate, which not only achieves the purpose of carbon emission reduction, but also can produce by-products for profit, thus killing two birds with one stone.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions: A method for enriching carbon dioxide from cement kiln tail gas and co-producing nano-calcium carbonate, using cement kiln tail gas to enrich carbon dioxide and jointly prepare nano-calcium carbonate; the method comprises the following steps: (1) Pre-treat the cement kiln exhaust gas, including dust removal, cooling, pressurization and spraying processes; (2) Removal of water from tail gas after pretreatment; (3) The dried tail gas enters the pressure swing adsorption process, and is processed through adsorption, pressure equalization and pressure reduction, displacement, vacuuming, pressure equalization and pressure increase, and finally pressure increase to complete the enrichment of carbon dioxide; (4) The enriched carbon dioxide gas enters the concentration adjustment process, is mixed with the dry tail gas pretreated in step (2), and is adjusted into a carbon dioxide mixed gas with a volume concentration of 35-45% and sent to the nano-calcium carbonate carbonization device; (5) Use quicklime and water to carry out digestion reaction to obtain 7-20% concentration Ca(OH)2 slurry, or use calcium hydroxide and water to mix to prepare 7-20% concentration Ca(OH)2 slurry, put it into the carbonization reactor after removing impurities, stir it at 18-35°C, and introduce enriched and prepared CO2 mixed gas to carry out carbonization reaction; the solid waste generated in the impurity removal process mainly consists of silicon dioxide (70%), calcium carbonate (25%) and calcium hydroxide (5%), and this part of waste can be recycled to the cement kiln for use as raw materials.

[0008] (6) Add the crystal form control agent and surfactant 1 10 minutes before carbonization and stir evenly, then continue the reaction until the conductivity value of the slurry in the carbonization reactor drops to the lowest point of 0.3-0.5ms / cm, stop the carbonization reaction, and obtain calcium carbonate; wherein surfactant 1 is C 12 -C 18 One or more fatty acids, added in an amount of 1.0-3.5% of the Ca(OH)2 slurry; (7) Adding surfactant 2 to the calcium carbonate after the carbonization reaction in step (6) for stirring and activation, and filtering the obtained slurry, drying, and crushing to obtain active nano calcium carbonate, wherein surfactant 2 is C 12 -C 18 One or more sodium salts of fatty acids, added in an amount of 0.5-1.5% of the Ca(OH)2 slurry.

[0009] The nano calcium carbonate produced by the method is an active product with hydrophobic surface.

[0010] Preferably, in step (1), the dust removal efficiency is 99%, the tail gas is cooled to 40±2°C, pressurized to 0.12MPa, and sprayed to remove SO2, ammonia, dust, and VOCs, so that the SO2 content of the tail gas after pretreatment is less than 0.1mg / m 3 .

[0011] Preferably, the dehydration in step (2) is carried out by three-tower adsorption dehydration, wherein the adsorbent used is one or more of activated alumina, silica balls, and aluminosilicate molecular sieves.

[0012] Preferably, the dehydration in step (2) adopts 2 towers for adsorption dehydration and 1 tower for regeneration, in alternating cycles, and the process includes 4 steps of adsorption, inversion, vacuuming and final pressurization, wherein the adsorbent used is one or more of activated alumina, silica balls and aluminosilicate molecular sieves.

[0013] Preferably, the carbon dioxide adsorbent in step (3) comprises one or more of activated carbon, zeolite, liquid organic amine, and photosensitive adsorption material.

[0014] Preferably, the volume content of CO2 after the pressure swing adsorption treatment in step (3) reaches 85% or more.

[0015] Preferably, the temperature of the CO2 mixed gas after preparation in step (4) is controlled in the range of 35-40°C.

[0016] Preferably, in step (5), if quicklime and water are used to prepare the Ca(OH)2 slurry, the calcium oxide content of the quicklime is ≥95%, and the activity is greater than 350 ml / 4N-HCl; if calcium hydroxide is used to prepare the Ca(OH)2 slurry, the calcium hydroxide content in the calcium hydroxide raw material is ≥98%, and the whiteness is ≥92%.

[0017] Preferably, in step (6), the crystal form controlling agent is one or a mixture of citric acid, sucrose, and polyphosphate, and the total added amount is 0.5-2.5% of the Ca(OH)2 slurry.

[0018] Preferably, the drying temperature in step (7) is 115-130°C.

[0019] Preferably, the pulverizing and classifying in step (7) refers to pulverizing and classifying the finished product so that its apparent powder particle size D97≤9 μm.

[0020] Preferably, the nano-calcium carbonate with a narrow particle size distribution in step (7) refers to nano-calcium carbonate with a primary particle size of 40-100 nm.

[0021] Compared with the prior art, the beneficial effects of the present invention are: In step (6) and step (7), the present invention completes the surface coating under alkaline conditions during the calcium carbonate formation period, thereby improving production efficiency, and the product quality and cost are superior to the traditional process of organic coating after calcium carbonate formation.

[0022] This process makes full use of the carbon dioxide in the exhaust gas of the cement kiln, enriches the carbon dioxide and then prepares nano calcium carbonate with purchased calcium oxide or calcium hydroxide. It not only solves the problem of carbon emission reduction in the cement industry, but also creates a profit model for by-products in the cement industry, killing two birds with one stone.

[0023] The nano calcium carbonate produced by the method of the invention has the characteristics of cubic shape, primary particle size of 40-100nm and apparent particle size D97≤9um, and can be widely used in rubber, plastic, silicone rubber and other industrial fields as a functional filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Attached Figure 1This is a comparison diagram of the process flow of the present invention (left) and the process flow of the traditional nano calcium carbonate production process (right); Attached Figure 2 It is the carbonization conductivity diagram of the process of the present invention; Attached Figure 3 This is the conductivity diagram of the conventional nano calcium carbonate process of the present invention; Attached Figure 4 This is an electron microscope image of the nano-calcium carbonate obtained in Example 1 of the present invention; Attached Figure 5 This is an electron microscope image of the nano calcium carbonate obtained in the first batch of Comparative Example 1 of the present invention; Attached Figure 6 This is an electron microscope image of the nano-calcium carbonate obtained in Example 2 of the present invention; Attached Figure 7 This is an electron microscope image of the nano-calcium carbonate obtained in the second batch of Comparative Example 1 of the present invention; Attached Figure 8 This is a laser particle size diagram of nano calcium carbonate obtained in Example 1 of the present invention; Attached Fig. 9 This is the laser particle size diagram of the nano calcium carbonate obtained in the first batch of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the application. Example 1

[0026] A method for enriching carbon dioxide from cement kiln tail gas and co-producing nano-calcium carbonate, comprising: Tail gas pretreatment: Take the cement kiln tail gas at the entrance of the raw material mill, remove the dust, and the dust removal efficiency is 99.1%; cool it to 38℃; pressurize it to 0.12Mpa; spray desulfurization to reduce the SO2 content to 0.097mg / m 3 .

[0027] Tail gas dehydration: Tail gas enters the dehydration tower, in which the dehydrating agent is activated alumina.

[0028] Carbon dioxide adsorption: The tail gas enters the adsorption tower after dehydration. The carbon dioxide adsorbent is activated carbon and liquid organic amine, with a mass ratio of 7:3. The volume concentration of carbon dioxide after adsorption is 87.4%.

[0029] Carbon dioxide preparation: After adsorption, the carbon dioxide enters the gas pressure-stabilizing tank and is introduced into the air for concentration adjustment. The volume concentration of carbon dioxide is adjusted to 36.8% and the temperature is 38.2°C.

[0030] Slurry preparation: Purchase high-quality quicklime with a calcium oxide content of 95.0% and a lime activity of 350ml / 4N-HCl, and react it with 65°C hot water to obtain Ca(OH)2 slurry, which is then added with water to prepare a turbid liquid with a Ca(OH)2 mass concentration of 7±0.1%.

[0031] Carbonization: Add 1.5 cubic meters of calcium hydroxide slurry with a mass concentration of 7±0.1% into a 2 cubic meter reactor. The starting temperature of carbonization is 28°C. Pass 36.8% carbon dioxide gas by volume for carbonization. Add 0.4 kg of sucrose, 0.8 kg of citric acid, and 2.4 kg of octadecyl fatty acid (surfactant 1) before and after the start of carbonization. Then carry out carbonization reaction until the pH value of the calcium carbonate slurry reaches 7 and the minimum conductivity (0.4 ms / cm). Then stop the reaction. The carbonization time is controlled within 50-55 minutes. Then add 1.8 kg of sodium salt of octadecyl fatty acid (surfactant 2) and activate for 30 minutes.

[0032] The slurry is filtered, washed, flash dried at 110-120°C, and then crushed and classified to obtain nano calcium carbonate.

[0033] The particle size of nano calcium carbonate is 40-60nm (attached electron microscope photo, see Figure 3 As shown), the specific surface area was determined to be 24.15 m 2 / g, the powder D97 of this product is 5.13um (attached with laser particle size, see Figure 7 As shown), the product has a whiteness of 93.1% and a cubic crystal shape.

[0034] Comparative Example 1.1: Based on Example 1, in this comparative example, the cement kiln tail gas was not dusted (dust removal rate 0%), and the remaining steps were the same as in Example 1.

[0035] The particle size of the obtained nano calcium carbonate is 40-80nm, and the measured specific surface area is 21.43m 2 / g, the powder D97 of this product is 7.13um, the whiteness of the product is 67.4%, and the crystal form is spindle. The whiteness and crystal form of the product do not meet the requirements.

[0036] Comparative Example 1.2: Based on Example 1, the cement kiln in this comparative example does not desulfurize, and the SO2 content is 0.14 mg / m 3 , the remaining steps are the same as those in Example 1.

[0037] The particle size of the obtained nano calcium carbonate is 40-80nm, and the measured specific surface area is 20.33m 2 / g, the powder D97 of this product is 5.33um, the whiteness of the product is 90.4%, and the crystal form is chain-like. The crystal form of the product does not meet the requirements. Example 2

[0038] Tail gas pretreatment: Take the cement kiln tail gas at the entrance of the raw material mill, remove the dust, and the dust removal efficiency is 99.1%; cool it to 38℃; pressurize it to 0.12Mpa; spray desulfurization to reduce the SO2 content to 0.097mg / m 3 .

[0039] Tail gas dehydration: Tail gas enters the dehydration tower, in which the dehydrating agent is activated alumina.

[0040] Carbon dioxide adsorption: The tail gas enters the adsorption tower after dehydration. The carbon dioxide adsorbent is activated carbon and liquid organic amine, with a mass ratio of 7:3. The volume concentration of carbon dioxide after adsorption is 87.4%.

[0041] Carbon dioxide preparation: After adsorption, the carbon dioxide enters the gas pressure-stabilizing tank and is introduced into the air for concentration adjustment. The volume concentration of carbon dioxide is adjusted to 36.8% and the temperature is 38.2°C.

[0042] Slurry preparation: Purchase high-quality quicklime with a calcium oxide content of 95.0% and a lime activity of 350ml / 4N-HCl, and react it with 65°C hot water to obtain Ca(OH)2 slurry, which is then added with water to form a turbid liquid with a Ca(OH)2 mass concentration of 20±0.1%.

[0043] Carbonization: Add 1.5 cubic meters of calcium hydroxide slurry with a mass concentration of 20±0.1% into a 2 cubic meter reactor. The starting temperature of carbonization is 21°C. Pass 36.8% carbon dioxide gas by volume for carbonization. Add 0.4 kg of sucrose, 0.8 kg of citric acid, and 2.4 kg of octadecane fatty acid (surfactant 1) before and after the start of carbonization. Then carry out carbonization reaction until the pH value of the calcium carbonate slurry reaches 7 and the conductivity reaches the minimum value (0.4 ms / cm). Then stop the reaction. The carbonization time is controlled within 50-55 minutes. Then add 1.8 kg of octadecane fatty acid sodium salt (surfactant 2) and activate for 30 minutes.

[0044] The slurry is filtered, washed, flash dried at 110-120°C, and then crushed and classified to obtain nano calcium carbonate.

[0045] The particle size of nano calcium carbonate is 80-100nm (attached electron microscope photo, see Figure 5 As shown in the figure), the specific surface area was determined to be 17.28 m 2 / g, the powder D97 of this product is 6.87um, the product whiteness is 94.1%, and the crystal form is cubic. Example 3

[0046] Tail gas pretreatment: Take the cement kiln tail gas at the entrance of the raw material mill, remove the dust, and the dust removal efficiency is 99.2%; cool it to 38℃; increase the pressure to 0.12Mpa; spray desulfurization to reduce the SO2 content to 0.097mg / m 3 .

[0047] Tail gas dehydration: Tail gas enters the dehydration tower, in which the dehydrating agents are activated silica balls and aluminum silicate.

[0048] Carbon dioxide adsorption: The tail gas enters the adsorption tower after dehydration. The carbon dioxide adsorbent is activated carbon and zeolite with a mass ratio of 5:5. The volume concentration of carbon dioxide after adsorption is 88.1%.

[0049] Carbon dioxide preparation: After adsorption, the carbon dioxide enters the gas pressure-stabilizing tank and is introduced into the air for concentration adjustment. The volume concentration of carbon dioxide is adjusted to 38.4% and the temperature is 38.1°C.

[0050] Slurry preparation: Purchase high-quality quicklime with a calcium oxide content of 95.0% and a lime activity of 350ml / 4N-HCl, and react it with 65°C hot water to obtain Ca(OH)2 slurry, which is then added with water to prepare a turbid liquid with a Ca(OH)2 mass concentration of 7±0.1%.

[0051] Carbonization: Add 1.5 cubic meters of calcium hydroxide slurry with a mass concentration of 7±0.1% into a 2 cubic meter reactor. The starting temperature of carbonization is 28°C. Pass 38.4% carbon dioxide gas by volume for carbonization. Add 0.6 kg of sucrose, 0.6 kg of phosphate, and 2.2 kg of 14-carbon fatty acid (surfactant 1) before and after the start of carbonization. Then carry out carbonization reaction until the pH value of the calcium carbonate slurry reaches 7 and the minimum conductivity (0.4 ms / cm). Then stop the reaction. The carbonization time is controlled within 50-55 minutes. Then add 2.2 kg of sodium salt of 16-carbon fatty acid (surfactant 2) and activate for 30 minutes.

[0052] The slurry is filtered, washed, flash dried at 110-120°C, and then crushed and classified to obtain nano calcium carbonate.

[0053] The particle size of nano calcium carbonate is 40-60nm, and the measured specific surface area is 23.93m 2 / g, the powder D97 of this product is 5.36um, the product whiteness is 93.4%, and the crystal form is cubic. Example 4

[0054] Tail gas pretreatment: Take the cement kiln tail gas at the entrance of the raw material mill, remove the dust, and the dust removal efficiency is 99.1%; cool it to 38℃; pressurize it to 0.12Mpa; spray desulfurization to reduce the SO2 content to 0.097mg / m 3 .

[0055] Tail gas dehydration: Tail gas enters the dehydration tower, where the dehydrating agents are activated alumina and silica balls.

[0056] Carbon dioxide adsorption: The tail gas enters the adsorption tower after dehydration. The carbon dioxide adsorbent is zeolite and liquid organic amine, with a mass ratio of 6:4. The volume concentration of carbon dioxide after adsorption is 88.1%.

[0057] Carbon dioxide preparation: After adsorption, the carbon dioxide enters the gas pressure-stabilizing tank and is introduced into the air for concentration adjustment. The volume concentration of carbon dioxide is adjusted to 44.8% and the temperature is 35.2°C.

[0058] Slurry preparation: Purchase high-quality quicklime with a calcium oxide content of 98.0% and a lime activity of 355ml / 4N-HCl, and react it with 65°C hot water to obtain Ca(OH)2 slurry, which is then added with water to prepare a turbid liquid with a Ca(OH)2 mass concentration of 20±0.1%.

[0059] Carbonization: Add 1.5 cubic meters of calcium hydroxide slurry with a mass concentration of 20±0.1% into a 2 cubic meter reactor. The starting temperature of carbonization is 18°C. Pass 44.8% carbon dioxide gas by volume for carbonization. Add 0.6 kg of sucrose, 0.8 kg of citric acid, and 2.0 kg of octadecane fatty acid (surfactant 1) before and after the start of carbonization. Then carry out carbonization reaction until the pH value of the calcium carbonate slurry reaches 7 and the minimum conductivity (0.4 ms / cm). Then stop the reaction. The carbonization time is controlled within 50-55 minutes. Then add 1.8 kg of octadecane fatty acid sodium salt (surfactant 2) and activate for 30 minutes.

[0060] The slurry is filtered, washed, flash dried at 110-120°C, and then crushed and classified to obtain nano calcium carbonate.

[0061] The particle size of nano calcium carbonate is 80-100nm, and the measured specific surface area is 18.28m 2 / g, the powder D97 of this product is 7.87um, the product whiteness is 93.8%, and the crystal form is cubic.

[0062] Comparative Example 4.1: Based on Example 4, in this comparative example, the type of surfactant 1 is a 16-carbon fatty acid salt, the type of surfactant 2 is a 16-carbon fatty acid salt, and the remaining steps are the same as Example 4.

[0063] The particle size of the obtained nano calcium carbonate is 80-100nm, and the measured specific surface area is 17.28m 2 / g, the powder D97 of this product is 7.47um, the product whiteness is 93.4%, and the crystal form is cubic.

[0064] Comparative Example 4.2: Based on Example 4, the content of the purchased calcium oxide product in this comparative example is 94%, the activity of lime is 340 ml / 4N-HCl, and the remaining steps are the same as Example 6.

[0065] The particle size of the obtained nano calcium carbonate is 90-120nm, and the measured specific surface area is 14.56m 2 / g, the powder D97 of this product is 6.47um, the whiteness of the product is 93.9%, and the crystal form is spindle. The particle size, specific surface area and crystal form do not meet the requirements.

[0066] Based on the data of the above embodiments and comparative examples, the nano-calcium carbonate obtained in Embodiment 1 and Embodiment 2 has better quality, and the products are all cubic nano-calcium carbonate particles with narrow and uniform particle size distribution range. Therefore, Embodiment 1 and Embodiment 2 are preferred embodiments of this process.

[0067] Comparative Example 1 This comparative example is a method for preparing nano calcium carbonate using a traditional process.

[0068] Limestone with a calcium carbonate content of 98.5% is calcined by high-temperature radiation to generate CaO and CO2 gas. High-quality quicklime is digested with water to obtain Ca(OH)2 slurry. CO2 gas is used as the gas source for carbonization reaction. The above raw materials are carbonized, the carbonized slurry is filter-pressed, washed, flash-dried at 110-120°C, and then crushed and classified to obtain the finished product.

[0069] Two batches of finished products were taken for testing.

[0070] Finished product 1: The particle size of the finished product is 50-70nm (attached with electron microscope photo, see Figure 4 ), the specific surface area was determined to be 23.67 m 2 / g, the powder D97 of this product is 6.26um (attached with laser particle size, see Figure 8 as shown).

[0071] Finished product 2: The particle size of the finished product is 40-80nm (attached with electron microscope photo, see Figure 6 ), the specific surface area was determined to be 22.67 m 2 / g, the powder D97 of this product is 6.86um.

[0072] Compared with the traditional process, this process makes full use of the carbon dioxide in the tail gas of cement kilns, which not only achieves the goal of energy conservation and emission reduction, but also can use this part of carbon dioxide to prepare by-products, thereby further increasing revenue and covering the investment cost of energy conservation and emission reduction, which can be said to kill two birds with one stone. In addition, the product produced by enriching carbon dioxide from cement kiln tail gas and co-producing nano calcium carbonate is not inferior to the existing process in terms of quality, and the powder particle size is more uniform, which can maintain a certain advantage in product competition.

Claims

1. A method for enriching carbon dioxide from cement kiln tail gas and producing nano-calcium carbonate, characterized in that: Using cement kiln tail gas to enrich carbon dioxide and jointly prepare nano calcium carbonate; the method comprises the following steps: (1) Pre-treat the cement kiln exhaust gas, including dust removal, cooling, pressurization and spraying processes; (2) Removal of water from tail gas after pretreatment; (3) The dried tail gas enters the pressure swing adsorption process, and is processed through adsorption, pressure equalization and pressure reduction, displacement, vacuuming, pressure equalization and pressure increase, and finally pressure increase to complete the enrichment of carbon dioxide; (4) The enriched carbon dioxide gas enters the concentration adjustment process, is mixed with the dry tail gas pretreated in step (2), and is adjusted into a carbon dioxide mixed gas with a volume concentration of 35-45% and sent to the nano-calcium carbonate carbonization device; (5) Use quicklime and water to carry out digestion reaction to obtain 7-20% concentration Ca(OH)2 slurry, or use calcium hydroxide and water to mix to prepare 7-20% concentration Ca(OH)2 slurry, after removing impurities, put it into the carbonization reactor, stir at 18-35°C, and introduce the enriched and prepared CO2 mixed gas to carry out carbonization reaction; (6) Add the crystal form control agent and surfactant 1 10 minutes before carbonization and stir evenly, then continue the reaction until the conductivity value of the slurry in the carbonization reactor drops to the lowest point of 0.3-0.5ms / cm, stop the carbonization reaction, and obtain calcium carbonate; wherein surfactant 1 is C 12 -C 18 One or more fatty acids, added in an amount of 1.0-3.5% of the Ca(OH)2 slurry; (7) Adding surfactant 2 to the calcium carbonate after the carbonization reaction in step (6) for stirring and activation, and filtering the obtained slurry, drying, and crushing to obtain active nano calcium carbonate, wherein surfactant 2 is C 12 -C 18 One or more sodium salts of fatty acids, added in an amount of 0.5-1.5% of the Ca(OH)2 slurry.

2. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: In step (1), the dust removal efficiency is 99%, the tail gas is cooled to 40±2°C, pressurized to 0.12MPa, and sprayed to remove SO2, ammonia, dust, and VOCs, so that the SO2 content of the tail gas after pretreatment is less than 0.1mg / m 3 .

3. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: The dehydration in step (2) adopts three-tower adsorption dehydration, wherein the adsorbent used is one or more of activated alumina, silica balls, and aluminosilicate molecular sieves.

4. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: In step (2), dehydration is carried out by using two towers for adsorption dehydration and one tower for regeneration in alternating cycles. The process includes four steps: adsorption, inversion, vacuuming, and final pressure increase. The adsorbent used is one or more of activated alumina, silica balls, and aluminosilicate molecular sieves.

5. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: The carbon dioxide adsorbent in step (3) includes one or more of activated carbon, zeolite, liquid organic amine, and photosensitive adsorption material.

6. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: The volume content of CO2 after the pressure swing adsorption treatment in step (3) reaches 85% or more.

7. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: The temperature of the CO2 mixed gas after preparation in step (4) is controlled in the range of 35-40°C.

8. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: In the step (5), if quicklime and water are used to prepare the Ca(OH)2 slurry, the calcium oxide content of the quicklime is ≥95%, and the activity is greater than 350 ml / 4N-HCl; if calcium hydroxide is used to prepare the Ca(OH)2 slurry, the calcium hydroxide content in the calcium hydroxide raw material is ≥98%, and the whiteness is ≥92%.

9. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: In step (6), the crystal form control agent is one or a mixture of citric acid, sucrose, and polyphosphate, and the total added amount is 0.5-2.5% of the Ca(OH)2 slurry.

10. The method for co-producing nano-calcium carbonate by enriching carbon dioxide from cement kiln tail gas according to claim 1, characterized in that: The drying temperature in step (7) is 115-130°C.

Citation Information

Patent Citations

  • Method for high-concentration carbonization production of spherical nano calcium carbonate

    CN102701255A

  • Method for producing nano calcium carbonate by using tail gas generated by waste treatment

    CN113880127A

  • Method for capturing and comprehensively utilizing carbon dioxide

    CN115350581A